1990
DOI: 10.3919/ringe1963.51.327
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Lymphangioma of the Jejunum and a Review of 28 Cases in Japan

Abstract: Lymphangioma of the small intestine is so rare that only 28 cases have been reported in Japan. This paper describes a case of lymphagioma of the jejunum, together with a review of the literature. A 30-year-old woman was admitted to our hospital with the chief complaints of nausea and lumbago. Urinalysis, haematological and biochemical screening were normal. Ultrasonography and computed tomography filled with a clear yellow fluid was found in the jejunum 140cm distant from the Treitz's ligament. Partial resecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The mass is usually discovered only incidentally during examination or operation for an unrelated complaint. 11,12 However, some patients have acute clinical symptoms because of compression of the adjacent structures or because of complications such as infection, perforation, torsion, and rupture. 13,14 It has also been reported that intestinal lymphangioma causes intestinal obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The mass is usually discovered only incidentally during examination or operation for an unrelated complaint. 11,12 However, some patients have acute clinical symptoms because of compression of the adjacent structures or because of complications such as infection, perforation, torsion, and rupture. 13,14 It has also been reported that intestinal lymphangioma causes intestinal obstruction.…”
Section: Discussionmentioning
confidence: 99%